Metal supply method for metal-air fuel cell
Through the redox-mediated metal-air fuel cell system, the use of alkali metal composite materials and redox mediators, the replenishment fuel difficulties and electrode passivation problems of traditional zinc-air batteries are solved, and the volume energy density and safety are improved. Efficient recharge and low-cost maintenance are achieved.
Patent Information
- Application Number
- CN202380042873.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-03-28
- Filing Date
- 2023-03-28
- Publication Date
- 2025-01-03
AI Technical Summary
Traditional mechanically rechargeable zinc-air batteries have difficulties in recharge fuel processes and electrode passivation problems, and traditional zinc-based batteries lack volume energy density and safety.
Using a redox-mediated metal-air fuel cell system, a redox mediator such as 7,8-dihydroxy-2-phenylazine sulfonic acid and Co( III) TiPA, combined with an ion selective film and gas diffusion electrode, achieves efficient recharge of zinc metal and protection of electrode materials.
It significantly improves the feasibility of the fuel replenishment process, solves the problem of electrode passivation, improves volume energy density and safety, reduces maintenance costs, and achieves high energy density and good scalability.
Smart Images

Figure CN119256404A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to metal-air fuel cells and methods of supplying metal in a redox mediated metal-air fuel cell system to recharge the metal-air fuel cell system. Background Art
[0002] The listing or discussion of a previously published document in this specification should not be taken as an admission that the document is part of the prior art or is common general knowledge.
[0003] Flow batteries are similar to electrochemical cells, except that instead of an electrolyte being stored around the electrodes in the cell, an ionic solution is stored outside the cell and can be fed into the cell to generate electricity.
[0004] Zinc-based flow batteries have attracted considerable attention due to their low material cost, high cell voltage, high earth abundance, and low toxicity. However, conventional mechanically rechargeable zinc-air batteries have a relatively difficult "refueling" process and face electrode passivation issues.
[0005] Therefore, there is a need for a new rechargeable redox-mediated metal-air fuel cell system that possesses ultra-high energy density, excellent operating flexibility, good scalability, low cost, and superior safety for various energy storage applications and can overcome at least one of the above-mentioned problems. Summary of the invention
[0006] Aspects and embodiments of the present invention that address the above issues are provided in the following numbered clauses.
[0007] 1. A redox-mediated metal-air fuel cell system comprising:
[0008] A redox flow battery comprising:
[0009] A cathode chamber comprising one of the following:
[0010] a cathode electrode, and an inlet and an outlet adapted to bubble a gas through the cathode chamber;
[0011] or a gas diffusion air electrode for oxygen reduction reaction (ORR) by passing supply air through the cathode chamber;
[0012] an anode chamber comprising an anode electrode and an inlet adapted to receive anolyte from the first tank and an outlet adapted to provide anolyte to the first tank;
[0013] an ion selective membrane between the cathode chamber and the anode chamber; and
[0014] a first tank adapted to contain an anolyte and a redox mediated metal-air fuel cell cartridge and having an inlet adapted to receive the anolyte from the anode chamber and an outlet adapted to provide the anolyte to the anode chamber, wherein:
[0015] The redox-mediated metal-air fuel cell kit contains:
[0016] a cartridge housing; and
[0017] A composite material comprising:
[0018] A metal selected from alkali metals, alkaline earth metals, aluminum, zinc or iron;
[0019] Conductive carbon material; and
[0020] Binder.
[0021] 2. The system according to claim 1, wherein the metal is selected from one or more selected from the group consisting of Zn, Li, Na, K, Mg, Ca, Al and Fe.
[0022] 3. The system according to clause 2, wherein the metal is Zn.
[0023] 4. A system according to any of the preceding clauses, wherein the binder is selected from one or more of ethylene cellulose, polyolefins and fluorothermoplastics, optionally wherein the fluorothermoplastics are selected from one or more of the group selected from PTFE and PVDF.
[0024] 5. The system of clause 4, wherein the binder is PVDF.
[0025] 6. A system according to any of the preceding clauses, wherein:
[0026] The metal is present in an amount of 50 to 95 wt %;
[0027] The conductive carbon material is present in an amount of 2.5 to 30 wt %;
[0028] The binder is present in an amount of 2.5 to 20 wt%.
[0029] 7. A system according to clause 6, wherein:
[0030] The metal is present in an amount of 80 to 92 wt %, such as about 90 wt %;
[0031] The conductive carbon material is present in an amount of 3 to 10 wt %, such as about 5 wt %;
[0032] The binder is present in an amount of about 3 to 10 wt %, such as about 5 wt %.
[0033] 8. A system according to any of the preceding clauses, wherein the metal source material is provided in particulate form.
[0034] 9. A system according to any of the preceding clauses, wherein the conductive carbon material is carbon black.
[0035] 10. The system according to any of the preceding clauses, wherein the anode chamber and the first tank further comprise an anolyte comprising an anodic redox mediator and an electrolyte.
[0036] 11. A system according to clause 10, wherein:
[0037] (a) an anodic redox mediator is selected from one or more of the group consisting of phenazine derivatives, anthraquinone derivatives and alloxazine derivatives, optionally wherein the anodic redox mediator is 7,8-dihydroxy-2-phenazine sulfonic acid; and / or
[0038] (b) the concentration of the anodic redox mediator is 0.01 to 2 M, such as about 0.4 M; and / or
[0039] (c) The electrolyte is selected from one or more of an aqueous NaOH solution, an aqueous KOH solution (e.g., a concentration of KOH in water is 3 M) and an aqueous LiOH solution (e.g., a concentration of LiOH in water is 3 M), optionally wherein the concentration of NaOH in water is 3 M.
[0040] 12. The system of clause 10 or clause 11, wherein when the cathode chamber comprises a cathode electrode and an inlet and an outlet adapted to bubble a gas through the cathode chamber, it further comprises a cathode electrolyte comprising a cathode redox mediator and an electrolyte.
[0041] 13. A system according to clause 12, wherein:
[0042] (a) a cathode redox mediator selected from the group consisting of Co(III)TiPA, cobalt triethanolamine complex [Co(TEA)] and anthraquinone-2,6-disulfonate (AQDS); and / or
[0043] (b) the concentration of the cathode redox mediator is 0.01 to 1 M, such as about 0.2 M; and / or
[0044] (c) The electrolyte is selected from one or more of an aqueous NaOH solution, an aqueous KOH solution (e.g., a concentration of KOH in water is 3 M) and an aqueous LiOH solution (e.g., a concentration of LiOH in water is 3 M), optionally wherein the concentration of NaOH in water is 3 M.
[0045] 14. A system according to any of the preceding clauses, wherein when the cathode chamber comprises a cathode electrode and an inlet and an outlet adapted to bubble a gas through the cathode chamber, the cathode chamber comprises:
[0046] cathode casing portion;
[0047] a cathode housed within the cathode casing portion; and
[0048] A second tank is adapted to contain catholyte, an inlet adapted to receive the catholyte from the cathode casing portion and an outlet adapted to provide the catholyte to the cathode casing portion, and an inlet and an outlet adapted to bubble a gas through the second tank.
[0049] 15. A system according to any one of clauses 1 to 10, wherein when the cathode chamber comprises a gas diffusion electrode, the cathode air electrode is selected from a porous carbon material coated with an oxygen reduction reaction catalyst, optionally wherein the oxygen reduction catalyst is selected from a platinum group metal (platinum or palladium), a non-platinum group noble metal (such as gold, silver), a carbon-based catalyst (such as a NiCo catalyst with N-doped carbon nanotubes as a carrier, a catalyst modified with dispersed Fe-N x One or more of the group consisting of substances and B-centered porous carbon).
[0050] 16. A redox-mediated metal-air fuel cell cartridge comprising:
[0051] a cartridge housing; and
[0052] A composite material comprising:
[0053] A metal selected from alkali metals, alkaline earth metals, aluminum, zinc or iron;
[0054] Conductive carbon material; and
[0055] Binder.
[0056] 17. The cartridge according to clause 16, wherein the metal is selected from one or more selected from the group consisting of Zn, Li, Na, K, Mg, Ca, Al and Fe.
[0057] 18. The cartridge according to clause 17, wherein the metal is Zn.
[0058] 19. The cartridge according to any one of clauses 16 to 18, wherein the binder is selected from one or more of ethylene cellulose, polyolefins and fluorothermoplastics, optionally wherein the fluorothermoplastics are selected from one or more of the group selected from PTFE and PVDF.
[0059] 20. The cartridge of clause 19, wherein the binder is PVDF.
[0060] 21. A cartridge according to any one of clauses 16 to 20, wherein:
[0061] The metal is present in an amount of 50 to 95 wt %;
[0062] The conductive carbon material is present in an amount of 2.5 to 30 wt %;
[0063] The binder is present in an amount of 2.5 to 20 wt%.
[0064] 22. A box according to clause 21, wherein:
[0065] The metal is present in an amount of 80 to 92 wt %, such as about 90 wt %;
[0066] The conductive carbon material is present in an amount of 3 to 10 wt %, such as about 5 wt %;
[0067] The binder is present in an amount of about 3 to 10 wt %, such as about 5 wt %.
[0068] 23. A cartridge according to any one of clauses 16 to 22, wherein the metal source material is provided in particulate form.
[0069] 24. A cartridge according to any one of clauses 16 to 23, wherein the conductive carbon material is carbon black.
[0070] 25. A method for supplying metal in a redox mediated metal-air fuel cell system, comprising:
[0071] A redox flow battery comprising:
[0072] A cathode chamber comprising one of the following:
[0073] a cathode electrode, and an inlet and an outlet adapted to bubble a gas through the cathode chamber;
[0074] an anode chamber comprising an anode electrode, an anolyte comprising an anodic redox mediator and an electrolyte, and an inlet adapted to receive the anolyte from the first tank and an outlet adapted to provide the anolyte to the first tank;
[0075] an ion selective membrane between the cathode chamber and the anode chamber; and
[0076] A first tank comprising an anolyte, a redox mediated metal-air fuel cell cartridge as described in any one of clauses 16 to 24, and an inlet adapted to receive the anolyte from the anode chamber and an outlet adapted to provide the anolyte to the anode chamber, wherein the method involves:
[0077] (a) circulating the anolyte from the first tank to the anode chamber and back again, and supplying gas to the catholyte; and
[0078] (b) When the redox mediated metal-air fuel cell cartridge is exhausted, the redox mediated metal-air fuel cell cartridge is replaced.
[0079] 26. A method according to clause 25, wherein:
[0080] (a) when the cathode chamber comprises a cathode electrode and an inlet and an outlet adapted to bubble a gas through the cathode chamber, the cathode redox mediator is selected from one or more of the group consisting of Co(III)TiPA, cobalt triethanolamine complex [Co(TEA)] and anthraquinone-2,6-disulfonate (AQDS), or;
[0081] (b) when the cathode chamber comprises a cathode electrode and an inlet and an outlet adapted to bubble a gas through the cathode chamber, the concentration of the cathode redox mediator is from 0.01 to 1 M, such as about 0.2 M; and / or
[0082] (c) an anodic redox mediator selected from one or more of the group consisting of phenazine derivatives, anthraquinone derivatives and alloxazine derivatives, optionally wherein the anodic redox mediator is 7,8-dihydroxy-2-phenazine sulfonic acid; and / or
[0083] (d) the concentration of the anodic redox mediator is 0.01 to 2 M, such as about 0.4 M; and / or
[0084] (e) The electrolyte is selected from one or more of an aqueous NaOH solution, an aqueous KOH solution (e.g., a concentration of KOH in water is 3 M) and an aqueous LiOH solution (e.g., a concentration of LiOH in water is 3 M), optionally wherein the concentration of NaOH in water is 3 M.
[0085] 27. A method according to clause 25 or clause 26, wherein when the cathode chamber comprises a cathode electrode and an inlet and an outlet adapted to bubble a gas through the cathode chamber, the cathode chamber comprises:
[0086] cathode casing portion;
[0087] a cathode housed within the cathode casing portion; and
[0088] A second tank is adapted to contain catholyte, an inlet adapted to receive the catholyte from the cathode casing portion and an outlet adapted to provide the catholyte to the cathode casing portion, and an inlet and an outlet adapted to bubble a gas through the second tank.
[0089] 28. A method according to clause 25, wherein:
[0090] (a) When the cathode chamber comprises a gas diffusion electrode for oxygen reduction reaction that allows air or oxygen to be supplied directly through the cathode chamber, the cathode air electrode is selected from a porous carbon material coated with an oxygen reduction reaction catalyst, optionally wherein the oxygen reduction catalyst is selected from a platinum group metal (platinum or palladium), a non-platinum group noble metal (e.g., gold, silver), a carbon-based catalyst (e.g., a NiCo catalyst with N-doped carbon nanotubes as a carrier, a catalyst modified with dispersed Fe-Nx One or more of the group consisting of:
[0091] (b) an anodic redox mediator selected from one or more of the group consisting of phenazine derivatives, anthraquinone derivatives and alloxazine derivatives, optionally wherein the anodic redox mediator is 7,8-dihydroxy-2-phenazine sulfonic acid; and / or
[0092] (c) the concentration of the anodic redox mediator is 0.01 to 2 M, such as about 0.4 M; and / or
[0093] (d) The electrolyte is selected from one or more of an aqueous NaOH solution, an aqueous KOH solution (e.g., a concentration of KOH in water of 3 M) and an aqueous LiOH solution (e.g., a concentration of LiOH in water of 3 M), optionally wherein the concentration of NaOH in water is 3 M.
[0094] 29. A metal-air fuel cell metal source material, wherein the source material comprises:
[0095] A metal selected from alkali metals, alkaline earth metals, aluminum, zinc or iron;
[0096] Conductive carbon material; and
[0097] Binder.
[0098] 30. A composite material comprising:
[0099] A metal selected from alkali metals, alkaline earth metals, aluminum, zinc or iron;
[0100] Conductive carbon material; and
[0101] Binder.
[0102] 31. The metal source material according to clause 29 or the composite material according to clause 28, wherein the metal is selected from one or more selected from the group consisting of Zn, Li, Na, K, Mg, Ca, Al and Fe.
[0103] 32. The metal source material or the composite material according to item 31, wherein the metal is Zn.
[0104] 33. A metal source material according to any one of clauses 29, 31 and 32 or a composite material according to any one of clauses 30 to 32, wherein the binder is selected from one or more of ethylene cellulose, polyolefins and fluorothermoplastics, optionally wherein the fluorothermoplastics are selected from one or more of the group selected from polytetrafluoroethylene (PTFE) and polyvinylidene fluoride (PVDF).
[0105] 34. The metal source material or the composite material according to clause 33, wherein the binder is PVDF.
[0106] 35. A metal source material according to any one of clauses 29 and 31 to 34 or a composite material according to any one of clauses 30 to 34, wherein:
[0107] The metal is present in an amount of 50 to 95 wt %;
[0108] Carbon black is present in an amount of 2.5 to 30 wt %; and
[0109] The binder is present in an amount of 2.5 to 20 wt%.
[0110] 36. The metal source material or the composite material according to clause 35, wherein:
[0111] The metal is present in an amount of 80 to 92 wt %, such as about 90 wt %;
[0112] The conductive carbon material is present in an amount of 3 to 10 wt%, such as about 5 wt%; and
[0113] The binder is present in an amount of about 3 to 10 wt %, such as about 5 wt %.
[0114] 37. A metal source material according to any one of clauses 29 and 31 to 36 or a composite material according to any one of clauses 30 to 36, wherein the metal source material is provided in particulate form.
[0115] 38. The metal source material according to any one of clauses 29 and 31 to 37 or the composite material according to any one of clauses 30 to 37, wherein the conductive carbon material is carbon black. BRIEF DESCRIPTION OF THE DRAWINGS
[0116] Figure 1 Schematic diagram of the construction and operation of a redox-mediated Zn-air fuel cell (RM-ZAFC) is depicted. In this setup, Zn is loaded in the anode fuel tank, while O2 is supplied to the cathode gas diffusion tank (GDT).
[0117] Figure 2 Depicted are 20 mM 7,8-dihydroxy-2-phenazinesulfonic acid (DHPS) and 20 mM [Zn(OH)4] 2- Cyclic voltammetry (CV) in 3 M NaOH. Scan rate: 10 mV / s.
[0118] Figure 3 Depicted is a schematic diagram of an anode can into which fuel Zn particles can be replenished after discharge.
[0119] Figure 4Depicted are (a) the voltage profile of a RM-ZAFC single cell with 20 mL 0.2 M Co(III)TiPA / 3 M NaOH (with continuous O 2 bubbling) as the catholyte and 35 mL 0.4 M DHPS / 3 M NaOH (loaded with Zn particles) as the anolyte. Electrode area: 5 cm 2 . Current density: 10mA / cm 2 (b) At 100 mA / cm 2 Voltage profile of the cell in (a) at a current density of . After each discharge process, the cell was rested for 2 h with continuous O2 bubbling for self-charging of the catholyte, and the 0.15 g Zn particles in the anode tank were replaced with fresh Zn particles. (c) Voltage profile of an extended test of the RM-ZAFC cell with 20 mL 0.2 M Co(III)TiPA / 3 M NaOH (with continuous O2 bubbling) as the catholyte and 250 mL 0.2 M DHPS / 3 M NaOH (loaded with Zn particles) as the anolyte. Electrode area: 1 cm 2 After loading the Zn particles, the catholyte self-charged until the open circuit voltage (OCV) of the cell increased to 1.05 V.
[0120] Figure 5 Polarization curves and power performance of a cell with 20 mL 0.2 M Co(III)TiPA / 3 M NaOH as catholyte and 35 mL 0.4 M DHPS-2H / 3 M NaOH as anolyte at different states of charge (SOC) are depicted. Electrode area: 1 cm 2 .
[0121] Figure 6 depicts Figure 4 Scanning electron microscope (SEM) images of Zn particles (a) before discharge and (b) after discharge from the last particle load in c, and (c, d) Figure 5 d. anode carbon felt after discharge, and Figure 5 X-ray diffraction (XRD) patterns of Zn particles and anode carbon felt in (e) before discharge and (f) after discharge.
[0122] Figure 7 (a) shows the construction of an exploded view and (b) a photograph of a 4-cell RM-ZAFC stack. (c) Voltage profile of a 4-cell RM-ZAFC stack with 20 mL 0.2 M Co(III)TiPA 3 M NaOH (with continuous O 2 bubbling) as the catholyte and 35 mL 0.4 M DHPS 3 M NaOH (loaded with Zn particles) as the anolyte. Electrode area: 1 cm 2 . Current density: 10mA / cm2 (d) Comparison of RM-ZAFC, conventional ZAB, and alkaline fuel cells in terms of energy density, cost, scalability, flexibility, power density, volumetric capacity, safety, and feasibility.
[0123] Figure 8 Depicted are (a) the voltage profile of a 4-cell RM-ZAFC stack with 20 mL 0.2 M Co(III)TiPA / 3 M NaOH continuously bubbling O2 as the catholyte and 35 mL 0.4 M DHPS / 3 M NaOH loaded with Zn particles as the anolyte. Electrode area: 1 cm 2 . Current density: 100mA / cm 2 After each discharge process, the cell rested for 1.5 h with continuous O2 bubbling for self-charging of the catholyte, and the Zn particles in the anode tank were replaced with fresh Zn particles. (b) Voltage profile of a 4-cell flow battery stack during self-charging and Zn replacement.
[0124] Fig. 9 Plotted at 50 mA / cm 2 The cathode was supplied with 1.5 bar dry oxygen and 0.4 mg / cm 2 Pt loading of 1000 nm was used for ORR, and the working temperature was 50° C. The membrane was FAAM15 and pretreated in 6 M KOH for more than 24 h.
[0125] Fig.10 A further schematic diagram of the construction and operation of a redox-mediated Zn-air fuel cell (RM-ZAFC) is depicted. In this setup, Zn is loaded in the anode fuel tank, while O2 is fed to the cathode gas diffusion tank (GDT). DETAILED DESCRIPTION
[0126] It has been surprisingly discovered that a redox-mediated metal-air fuel cell (RM-ZAFC) system can significantly improve the feasibility of the "refueling" process (discussed above) compared to conventional mechanically rechargeable zinc-air batteries. The RM-ZAFC can also solve the electrode passivation problem faced by traditional alkaline Zn-based batteries, significantly improve volumetric energy density and safety compared to traditional hydrogen fuel cells, and improve the open design provided in the RM-ZAFC and reduce maintenance costs. These advantages can be derived from the use of specific composite materials or metal-air fuel cell metal source materials disclosed herein, and therefore, the disclosed invention also relates to said materials and their applications.
[0127] Therefore, in a first aspect of the present invention, there is provided a metal-air fuel cell metal source material, wherein the source material comprises:
[0128] A metal selected from alkali metals, alkaline earth metals, aluminum, zinc or iron;
[0129] Conductive carbon material; and
[0130] Binder.
[0131] Therefore, in a second aspect of the present invention, there is provided a composite material comprising:
[0132] A metal selected from alkali metals, alkaline earth metals, aluminum, zinc or iron;
[0133] Conductive carbon material; and
[0134] Binder.
[0135] In the embodiments herein, the word "includes" may be interpreted as requiring the features mentioned, but not limiting the presence of other features. Alternatively, the word "includes" may also refer to situations where only the listed components / features are intended to exist (e.g., the word "includes" may be replaced by the phrase "consisting of" or "consisting essentially of". It is expressly contemplated that both the broader and narrower interpretations may be applied to all aspects and embodiments of the present invention. In other words, the word "includes" and its synonyms may be replaced by the phrase "consisting of" or the phrase "consisting essentially of" or their synonyms, and vice versa.
[0136] The phrase "consisting essentially of..." and its synonyms may be interpreted herein to mean that a material may have a small amount of impurities present. For example, the material may be greater than or equal to 90% pure, such as greater than 95% pure, such as greater than 97% pure, such as greater than 99% pure, such as greater than 99.9% pure, such as greater than 99.99% pure, such as greater than 99.999% pure, such as 100% pure.
[0137] As used herein, the singular forms "a," "an," and "the" include plural referents unless the context clearly dictates otherwise. Thus, for example, reference to "a composition" includes a mixture of two or more such components and reference to "a metal" includes a mixture of two or more such metals, etc.
[0138] As mentioned herein, the metal used in the composite material and therefore in the above-mentioned metal-air fuel cell metal source material and composite material can be an alkali metal, an alkaline earth metal, aluminum, zinc or iron. Any suitable metal can be used herein. Examples of suitable metals include, but are not limited to, Zn, Li, Na, K, Mg, Ca, Al, Fe and combinations thereof. In specific embodiments that may be mentioned herein, the metal can be Zn.
[0139] When used in this article, the binding agent is intended to ensure contact between the metal and the conductive carbon material, and the material is kept together in a desired form (e.g., particles and / or granules). The binding agent can be any suitable material for this purpose, and can be a material that is inert under the conditions found in the metal-air fuel cell. Any material with the above-mentioned properties can be used in embodiments of the present invention. Examples of suitable materials include, but are not limited to, ethylene cellulose, polyolefins, fluorinated thermoplastics and combinations thereof. In the specific embodiments that may be mentioned herein, the binding agent may be fluorinated thermoplastics. In the more specific embodiments that may be mentioned herein, the binding agent may be selected from one or both of polytetrafluoroethylene (PTFE) and polyvinylidene fluoride (PVDF). In the further embodiments that may be mentioned herein, the binding agent may be PVDF.
[0140] As will be appreciated, any suitable amount of metal, conductive carbon material, and binder may be used in the metal-air fuel source materials and composite materials disclosed herein. For example, when present in metal-air fuel source materials and composite materials, a suitable amount of metal may be in an amount of 50 to 95 wt%, such as 80 to 92 wt%, such as about 90 wt%. For example, when present in metal-air fuel source materials and composite materials, a suitable amount of conductive carbon material may be in an amount of 2.5 to 30 wt%, such as 3 to 10 wt%, such as about 5 wt%. For example, when present in metal-air fuel source materials and composite materials, a suitable amount of binder may be in an amount of 2.5 to 20 wt%, such as about 3 to 10 wt%, such as about 5 wt%.
[0141] For the avoidance of doubt, it is expressly contemplated that where multiple numerical ranges directed to the same feature are recited herein, the endpoints of each range are intended to be combined in any order to provide further contemplated (and implicitly disclosed) ranges. Thus, in particular, when present in metal-air fuel source materials and composite materials, suitable amounts of metal may be the following amounts:
[0142] 50 to 80 wt%, 50 to 90 wt%, 50 to 92 wt%, 50 to 95 wt%;
[0143] 80 to 90 wt%, 80 to 92 wt%, 80 to 95 wt%;
[0144] 90 to 92 wt%, 90 to 95 wt%; and
[0145] 92 to 95 wt%.
[0146] In another more specific embodiment of the present invention, a metal source material or a composite material according to the present invention may be disclosed, wherein:
[0147] The metal is present in an amount of 50 to 95 wt %;
[0148] Carbon black is present in an amount of 2.5 to 30 wt %; and
[0149] The binder is present in an amount of 2.5 to 20 wt%.
[0150] In yet further specific embodiments of the present invention, a metal source material or a composite material according to the present invention may be disclosed, wherein:
[0151] The metal is present in an amount of 80 to 92 wt %, such as about 90 wt %;
[0152] The conductive carbon material is present in an amount of 3 to 10 wt%, such as about 5 wt%; and
[0153] The binder is present in an amount of about 3 to 10 wt %, such as about 5 wt %.
[0154] The metal-air fuel source materials and composite materials disclosed herein can be provided in any suitable form. For example, these materials can be provided in the form of particles. For example, the particles can be large enough to remain in a cartridge housing (e.g., a cartridge housing suitable for a redox-mediated metal-air fuel cell system). For example, the particles can be in the form of particles.
[0155] Any suitable conductive carbon material can be used herein. For example, the conductive carbon material can be carbon black, graphene, graphite, carbon nanotubes, etc., and combinations thereof.
[0156] It has been surprisingly found that placing a redox mediated metal-air fuel cell cartridge in an anode can can generate electricity continuously, provided that the cartridge is replaced regularly. Therefore, in a third aspect of the present invention, there is provided a redox mediated metal-air fuel cell cartridge comprising:
[0157] a cartridge housing; and
[0158] A composite material comprising:
[0159] A metal selected from alkali metals, alkaline earth metals, aluminum, zinc or iron;
[0160] Conductive carbon material; and
[0161] Binder.
[0162] As will be appreciated, the composite material will be contained within a cartridge housing.
[0163] The cartridge housing may be any suitable cartridge housing useful in a redox flow battery.With respect to redox mediated metal-air fuel cell systems, some considerations for the size of the apertures in the cartridge are provided below.
[0164] For the avoidance of doubt, the composite material may be as described above. Therefore, for the sake of brevity, a complete description of the composite material is not included here.
[0165] As will be appreciated, the redox mediated metal-air fuel cell cartridge may be particularly suitable for use in a redox mediated metal-air fuel cell system. Therefore, in a fourth aspect of the present invention, there is provided a redox mediated metal-air fuel cell system comprising:
[0166] A redox flow battery comprising:
[0167] A cathode chamber comprising one of the following:
[0168] a cathode electrode, and an inlet and an outlet adapted to bubble a gas through the cathode chamber;
[0169] or a gas diffusion air electrode for oxygen reduction reaction (ORR) that passes supply air through the cathode chamber;
[0170] an anode chamber comprising an anode electrode and an inlet adapted to receive anolyte from the first tank and an outlet adapted to provide anolyte to the first tank;
[0171] an ion selective membrane between the cathode chamber and the anode chamber; and
[0172] a first tank adapted to contain an anolyte and a redox mediated metal-air fuel cell cartridge and having an inlet adapted to receive the anolyte from the anode chamber and an outlet adapted to provide the anolyte to the anode chamber, wherein:
[0173] The redox-mediated metal-air fuel cell kit contains:
[0174] a cartridge housing; and
[0175] A composite material comprising:
[0176] A metal selected from alkali metals, alkaline earth metals, aluminum, zinc or iron;
[0177] Conductive carbon material; and
[0178] Binder.
[0179] For the avoidance of doubt, the redox mediated metal-air fuel cell cartridges and composites are as described above.
[0180] As described above, the cathode chamber may be in the form of a cathode chamber having an inlet and an outlet suitable for bubbling gas through the cathode chamber. Alternatively, the cathode chamber may be in the form of a gas diffusion electrode for oxygen reduction reaction that supplies air or oxygen directly through the cathode chamber. The latter arrangement may have more in common with a conventional air cathode and, in embodiments of the present invention, may be used to replace the cathode chamber mentioned above.
[0181] In certain embodiments that may be mentioned herein, there is disclosed a redox flow battery comprising:
[0182] a cathode chamber comprising a cathode electrode, and an inlet and an outlet adapted for bubbling a gas through the cathode chamber;
[0183] an anode chamber comprising an anode electrode and an inlet adapted to receive anolyte from the first tank and an outlet adapted to provide anolyte to the first tank;
[0184] an ion selective membrane between the cathode chamber and the anode chamber; and
[0185] A first tank adapted to contain an anolyte and a redox mediated metal-air fuel cell cartridge as described herein and having an inlet adapted to receive the anolyte from the anode chamber and an outlet adapted to provide the anolyte to the anode chamber.
[0186] In certain embodiments, when the cathode chamber comprises a cathode electrode and an inlet and an outlet suitable for bubbling a gas through the cathode chamber, the cathode chamber comprises:
[0187] cathode casing portion;
[0188] a cathode housed within the cathode casing portion; and
[0189] a second tank adapted to contain a catholyte, an inlet adapted to receive the catholyte from the cathode casing portion and an outlet adapted to provide the catholyte to the cathode casing portion, and an inlet and an outlet adapted to bubble a gas through the second tank. Thus, in a more specific embodiment that may be mentioned herein, a redox flow battery is disclosed, comprising:
[0190] a cathode chamber comprising a cathode electrode, and an inlet and an outlet adapted for bubbling a gas through the cathode chamber;
[0191] an anode chamber comprising an anode electrode and an inlet adapted to receive anolyte from the first tank and an outlet adapted to provide anolyte to the first tank;
[0192] an ion selective membrane between the cathode chamber and the anode chamber; and
[0193] a first tank adapted to contain an anolyte and a redox mediated metal-air fuel cell cartridge as described herein and an inlet adapted to receive the anolyte from the anode chamber and an outlet adapted to provide the anolyte to the anode chamber, wherein
[0194] The cathode chamber contains:
[0195] cathode casing portion;
[0196] a cathode housed within the cathode casing portion; and
[0197] A second tank is adapted to contain catholyte, an inlet adapted to receive the catholyte from the cathode casing portion and an outlet adapted to provide the catholyte to the cathode casing portion, and an inlet and an outlet adapted to bubble a gas through the second tank.
[0198] The redox mediated metal-air fuel cell cartridge utilizes a cartridge housing. The housing should be porous to allow entry and exit of a liquid (e.g., an anolyte), but the porosity should be arranged so that the composite material contained therein cannot escape into the first tank in any appreciable amount. As will be appreciated, the size of the pores or holes within the housing will be determined in large part by the size of the composite material, which may be provided in any suitable form (e.g., particles).
[0199] As used herein, composite materials may be as defined above. Therefore, for the sake of brevity, a complete discussion of possible embodiments is not included here.
[0200] The two electrodes in the redox-mediated metal-air fuel cell system, i.e., the cathode and the anode, can be carbon, metal, or a combination thereof. Preferably, the two electrodes have a high surface area, with or without more than one catalyst, to facilitate the charge collection process. They can be made of carbon, metal, or a combination thereof. Examples of electrodes can be found in Skyllas-Kazacos et al., Journal of The Electrochemical Society, 2011, 158, R55-79 and Weber et al., Journal of Applied Electrochemistry, 2011, 41, 1137-64. The above discussion about the cathode may be particularly correct for a cathode electrode located in a cathode chamber having an inlet and outlet suitable for bubbling gas through the cathode chamber, such a chamber being suitable for use with a liquid cathode electrolyte.
[0201] As will be appreciated, the present disclosure may be applied to any suitable metal anode that can be used in a metal-air battery system, such as anodes made using alkali metals (e.g., Li, Na, and K), alkaline earth metals (e.g., Mg and Al), and first row transition metals (e.g., Fe and Zn), and combinations thereof.
[0202] As mentioned above, the cathode chamber may comprise an inlet and an outlet suitable for bubbling a gas through the cathode chamber.In some embodiments mentioned herein, the gas may be oxygen.
[0203] In addition, the anode chamber may include an inlet adapted to receive anolyte from the first tank and an outlet adapted to provide anolyte to the first tank. The inlet of the anode chamber may be fluidly connected to the first tank for receiving anolyte from the first tank, and the outlet of the anode chamber may be fluidly connected to the first tank for providing anolyte to the first tank. As described above, the first tank also includes an inlet adapted to receive anolyte from the anode chamber and an outlet adapted to provide anolyte to the anode chamber. The inlet of the first tank may be fluidly connected to the anode chamber for receiving anolyte from the anode chamber, and the outlet of the first tank may be fluidly connected to the anode chamber for providing anolyte to the anode chamber. Thus, it is possible to circulate the anolyte from the first tank to the anode chamber and back again.
[0204] When referred to herein, an ion selective membrane can be an electroactive charge balance ion conducting membrane (e.g., potassium, lithium, or sodium ion conducting membrane). The ion selective membrane prevents cross diffusion of redox mediators and allows the movement of electroactive charge balance ions (e.g., potassium ions, lithium ions, sodium ions, magnesium ions, aluminum ions, copper ions, protons, or combinations thereof). For example, the ion selective membrane can be Nafion TM Membrane, lithium phosphorus oxynitride glass, lithium thiophosphate glass, sodium phosphorus oxynitride glass, sodium thiophosphate glass, NASICON type lithium conductive glass ceramics, NASICON type sodium conductive glass ceramics, garnet type lithium or sodium conductive glass ceramics, ceramic nanofiltration membrane, lithium or sodium ion exchange membrane or a suitable combination thereof.
[0205] In some embodiments that may be mentioned herein, the cathode chamber may further include a cathode electrolyte comprising a cathode redox mediator and an electrolyte. In certain embodiments, these may be stored in a second tank. In additional or alternative embodiments, the anode chamber and the first tank may further include an anolyte comprising an anode redox mediator and an electrolyte. Thus, in certain embodiments that may be mentioned herein,
[0206] The anode chamber and the first tank may further include an anolyte comprising an anode redox mediator and an electrolyte; and / or
[0207] The cathode chamber (and the second tank when present) may further include a catholyte comprising a cathode redox mediator and an electrolyte.
[0208] A redox mediator refers to a compound present in (e.g., dissolved in) an electrolyte (catholyte or anolyte) and serves as a molecular shuttle for transferring charge between the corresponding electrode and the energy storage material during charging / discharging. The redox mediator transfers charge between the corresponding electrode and the energy storage material.
[0209] In the redox-mediated metal-air fuel cell system described herein, the cathode electrolyte may include any suitable cathode redox mediator. Suitable cathode redox mediators include, but are not limited to, Co(III)TiPA, cobalt triethanolamine complex [Co(TEA)], anthraquinone-2,6-disulfonate (AQDS) and combinations thereof. The cathode redox mediator may be provided in the cathode electrolyte at any suitable concentration. For example, in embodiments of the invention that may be mentioned herein, the concentration of the cathode redox mediator present in the electrolyte may be 0.01 to 1M, such as about 0.2M.
[0210] In certain embodiments of the present invention, the anolyte may include any suitable anodic redox mediator. For example, the anolyte may include an anodic redox mediator, and the anodic redox mediator includes, but is not limited to, phenazine derivatives, anthraquinone derivatives, oxazine derivatives, and combinations thereof. In specific embodiments that may be mentioned herein, the anodic redox mediator may be 7,8-dihydroxy-2-phenazine sulfonic acid. The anodic redox mediator may be provided in the anolyte at any suitable concentration. For example, in embodiments of the present invention that may be mentioned herein, the concentration of the anodic redox mediator present in the electrolyte may be from 0.01 to 2M, such as about 0.4M.
[0211] Phenazine derivatives that may be mentioned herein include those having one or more substituents selected from the group consisting of: -R a OR 3 , -R a SO3H, -R a COOH, -R a SO3M, -R a COOM, -R a N(R 3 )2X, -R a N(R 3 )2. -R a PO(OH)2, -R a SH, -R a PS(OH)2, -R a -O-PO(OH)2, -R a -O-PS(OH)2, -Ra -S-PS(OH)2 or -(OCH2CH2) n OR 3 , where R 3 Each independently represents H or C1-C5 alkyl; R a Each independently does not exist or is a C1-C5 alkyl group; M is a cation; X is an anion, and n is an integer ≥ 1, as disclosed in WO 2018 / 231926, and its phenazine derivatives are incorporated herein by reference.
[0212] Anthraquinone derivatives that may be mentioned herein may be those disclosed in WO 2012 / 147398, which is incorporated herein by reference.
[0213] The alloxazine derivatives that may be mentioned herein may be those disclosed in WO 2016 / 144909, which is incorporated herein by reference.
[0214] The electrolytes mentioned above in conjunction with the catholyte and the anolyte may contain a solvent and one or more ion-donating compounds or salts.
[0215] Suitable solvents for the electrolyte are water, which can be used alone or in combination with an organic solvent suitable for use in a fuel cell system. The organic solvent can be used as an additive to adjust the standard potential of the active material. Suitable organic solvents that may be mentioned herein include, but are not limited to, alcohols, carbonates, ethers, esters, ketones and nitrites.
[0216] As mentioned above, the electrolyte also includes one or more compounds or salts that provide ions. Any suitable material can be used for this ability. Non-limiting examples of suitable ions include, but are not limited to, carboxylic acids and salts formed by complementary ions. Suitable ions that may be mentioned herein include, but are not limited to, ammonium ions, lithium ions, sodium ions, potassium ions, magnesium ions, aluminum ions, copper ions, chloride ions, bromide ions, nitrate ions, and hydroxide ions (e.g., ammonium ions, lithium ions, sodium ions, potassium ions, chloride ions, optionally, wherein the electrolyte is formed by one or more of the group consisting of ammonium ions, potassium ions, and chloride ions (e.g., potassium ions and / or chloride ions)).
[0217] In some embodiments mentioned herein, the electrolyte may be selected from one or more of an aqueous NaOH solution, an aqueous KOH solution (e.g., a KOH concentration of about 3 M in water), and an aqueous LiOH solution (e.g., a LiOH concentration of about 3 M in water). For example, in certain embodiments mentioned herein, the electrolyte may be an aqueous NaOH solution having a concentration of about 3 M in water.
[0218] In an optional embodiment that may be mentioned herein, the cathode chamber may include a gas diffusion electrode for oxygen reduction reaction that allows the supply of air or oxygen to pass directly through the cathode chamber. In an additional embodiment, the anode chamber and the first tank may further include an anolyte comprising an anode redox mediator and an electrolyte. Therefore, in certain embodiments that may be mentioned herein,
[0219] The cathode chamber further comprises a gas diffusion electrode for oxygen reduction reaction for supplying air or oxygen directly through the cathode chamber; and the anode chamber and the first tank further comprise an anolyte comprising an anodic redox mediator and an electrolyte. The anolyte may be as described above.
[0220] As will be appreciated, when the metal in the redox mediated metal-air fuel cell cartridge is depleted, the redox mediated metal-air fuel cell cartridge in the first tank of the redox mediated metal-air fuel cell system can be replaced to continue to generate electricity. Therefore, in a fifth aspect of the present invention, there is provided a method for supplying metal in a redox mediated metal-air fuel cell system, comprising:
[0221] A redox flow battery comprising:
[0222] A cathode chamber comprising one of the following:
[0223] a cathode electrode, and an inlet and an outlet adapted to bubble a gas through the cathode chamber;
[0224] an anode chamber comprising an anode electrode, an anolyte comprising an anodic redox mediator and an electrolyte, and an inlet adapted to receive the anolyte from the first tank and an outlet adapted to provide the anolyte to the first tank;
[0225] an ion selective membrane between the cathode chamber and the anode chamber; and
[0226] a first tank comprising an anolyte, a redox mediated metal-air fuel cell cartridge as described herein, and an inlet adapted to receive the anolyte from an anode chamber and an outlet adapted to provide the anolyte to the anode chamber, wherein the method involves:
[0227] (a) circulating the anolyte from the first tank to the anode chamber and back again, and supplying gas to the catholyte; and
[0228] (b) When the redox mediated metal-air fuel cell cartridge is exhausted, the redox mediated metal-air fuel cell cartridge is replaced.
[0229] In certain embodiments, when the cathode chamber comprises a cathode electrode and an inlet and an outlet suitable for bubbling a gas through the cathode chamber, the cathode chamber may comprise:
[0230] cathode casing portion;
[0231] a cathode housed within the cathode casing portion; and
[0232] A second tank is adapted to contain catholyte, an inlet adapted to receive the catholyte from the cathode casing portion and an outlet adapted to provide the catholyte to the cathode casing portion, and an inlet and an outlet adapted to bubble a gas through the second tank.
[0233] The redox mediated metal-air fuel cell cartridge and the various components described above have been described above, and therefore, for the sake of brevity, a discussion of these components is omitted here.
[0234] Advantages associated with the presently disclosed invention include:
[0235] Release zinc metal from the electrodes into separate “fuel” tanks, making it feasible to “refuel” after zinc metal is depleted, compared to conventional mechanically rechargeable zinc-air batteries;
[0236] ●Solve the electrode passivation problem faced by traditional alkaline Zn-based batteries;
[0237] ● Presents a significantly increased volumetric capacity of the anolyte (1,866Ah / L, more than 30 times that of vanadium flow batteries and 1.5 times that of commercial 700bar high-pressure H2 tanks);
[0238] Based on metal anodes with excellent capacity and relatively low potential, which is different from other redox-targeted electrolytes;
[0239] ●Improved the open design set in RM-ZAFC;
[0240] ● Reduced maintenance prices;
[0241] ●Ultra-high energy density;
[0242] ·Excellent work flexibility;
[0243] Good scalability;
[0244] ·low cost;
[0245] Excellent safety profile; and
[0246] Applicability in various energy storage applications.
[0247] All features disclosed in this specification may be combined in any combination. Each feature disclosed in this specification may be replaced by an alternative feature serving the same, equivalent or similar purpose. Therefore, unless otherwise expressly stated, each feature disclosed is merely an example of a series of equivalent or similar features.
[0248] From the above description, those skilled in the art can easily determine the basic characteristics of the present invention, and without departing from its spirit and scope, various changes and modifications can be made to the present invention to adapt it to various uses and conditions. Therefore, other embodiments are also within the claims.
[0249] Hereinafter, embodiments of the present invention are described in more detail with reference to the following examples. However, the present disclosure is not limited thereto. In addition, content not described in the present disclosure can be fully understood by those skilled in the art and will not be shown in this article.
[0250] Example
[0251] Material
[0252] Polyvinylidene fluoride (PVDF) was purchased from Alfa Aesar. Zn powder (powder, particle size <63 μm, purity ≥98%) was purchased from Merck. Super P conductive carbon black (TIMCAL) was used as received. Other chemicals and reagents were purchased from Sigma-Aldrich and used without further purification. Graphite felt (6 mm thick) was purchased from SGL Carbon and heat treated at 400 °C in air for 16 h before use. Anion exchange membrane (Sustainion X37-50 T grade) was purchased from Dioxide Materials.
[0253] General procedure for the synthesis of 0.6 M Co(II)(TiPA) dissolved in 20 mL 3.0 M NaOH
[0254] To synthesize 0.6M Co(II)(TiPA) dissolved in 20mL 3.0M NaOH, 4.5g of Co(II) sulfate powder was dissolved in 10mL deionized water in a N2 glove box. When the Co compound was completely dissolved, 3.06g of TiPA was added to the solution. After 10min, 2.4g of NaOH was added dropwise to the solution. As soon as NaOH was added to the solution, the Co(II)(TiPA) complex began to form. The solution was then stirred for 1 day, and the precipitated Na2SO4 powder was removed by centrifugation.
[0255] General procedure for the synthesis of DHPS and DHPS / 3M NaOH
[0256] DHPS was synthesized using the same method as in the literature [J.Am.Chem.Soc.2021, 143, 223-231]. Considering that one DHPS molecule consumes three OH groups during the dissolution process, - , 0.4M DHPS / 3M NaOH was prepared by dissolving 0.4M DHPS in 4.2M NaOH.
[0257] Analytical techniques
[0258] SEM measurement
[0259] SEM images were collected with a Zeiss Supra 40 FESEM system. The samples were mounted on conductive carbon tape and exposed to a high energy electron beam emitted by a 5 kV electric field.
[0260] XRD measurement
[0261] XRD patterns were collected with a Bruker D8 diffractometer at room temperature under an accelerating voltage of 40 kV with Cu Ka (0.154 nm) radiation.
[0262] Example 1. Electrochemical measurements
[0263] CV measurements were performed using a 3-electrode cell consisting of a glassy carbon working electrode, a platinum plate counter electrode, and a Hg / HgO reference electrode. OCP measurements were performed using a PineInstruments rotating disk ring electrode device AFMSRCE equipped with a 5 mm diameter glassy carbon working electrode, a Hg / HgO reference electrode, and a platinum plate counter electrode. Rotation speed: 1000 rpm. All electrochemical tests were performed using an Autolab electrochemical workstation (Metrohm, PSTA30).
[0264] Example 2. Redox-mediated Zn-air fuel cell (RM-ZAFC)
[0265] The settings include: Figure 1 RM-ZAFC shown. Zn metal is released from the anode chamber into an easily accessible external storage tank. The reaction of Zn can then be accomplished via a redox-targeted process utilizing the redox mediator DHPS.
[0266] In RM-ZAFC, graphite felt (6 mm thick, SGL Carbon) was used for both the positive electrode and the negative electrode. The carbon felt was heat treated at 400 ° C in air for 16 hours. Sustainion X37-50 membrane was used to separate the cathode electrolyte and the anolyte, and the membrane was soaked overnight in 3M NaOH before use. Fluororubber gaskets and PTFE tubes (ColeParmer) were used to build the battery. 0.4M DHPS / 3M NaOH (loaded with Zn particles) as the anolyte was circulated by a peristaltic pump at a flow rate of 50mL / min. During the test, O2 was bubbled into the cathode and N2 was bubbled into the anolyte continuously at a flow rate of 0.5L / min.
[0267] Results and discussion
[0268] Figure 220 mM DHPS and 20 mM [Zn(OH)4] in 3 M NaOH are shown. 2- CV of DHPS / DHPS-2H. The potential ratio of Zn / [Zn(OH)4] 2- The value is about 414 mV higher, indicating that DHPS can oxidize Zn metal. During discharge, DHPS-2H is first oxidized to DHPS at the anode and circulates to the anode tank, where it first oxidizes Zn to [Zn(OH)4] 2- To regenerate. When [Zn(OH)4] 2- When the concentration of ZnO reaches the solubility limit, it will transform into a solid ZnO suspension, which may flow into the anode compartment and may cause blockage after long-term discharge.
[0269] Example 3. Box loaded with Zn particles
[0270] In order to solve the problem mentioned in Example 2, Zn particles consisting of 90wt.% Zn powder, 5wt.% carbon black and 5wt.% PVDF were prepared to contain the reaction of Zn and the discharge products thereof, thereby forming [Zn(OH)4] 2- It is converted into ZnO on the particle surface. Figure 3 As shown, the cartridge loaded with Zn particles is placed in the anode can. After zinc is exhausted, the cartridge can be easily removed and replaced with fresh Zn particles for continuous power generation.
[0271] Example 4. RM-ZAFC single cell with 0.2M Co(III)TiPA / 3M NaOH
[0272] A RM-ZAFC single cell with 0.2M Co(III)TiPA / 3M NaOH (with continuous O2 bubbling) as catholyte and 0.4M DHPS / 3M NaOH as anolyte was assembled. During the entire discharge process, the cartridge loaded with Zn particles (prepared in Example 3) was replaced 3 times.
[0273] Assembly and testing of flow batteries
[0274] for Figure 4 RM-ZAFC for long-term operation, with an active area of 5 cm 2 , and graphite felt (6 mm thick, SGLCarbon) was used for both the positive electrode and the negative electrode. Figure 5 RM-ZAFC used for power testing, four 1cm 2Toray carbon paper was used as electrodes on both sides. Carbon felt and carbon paper were heat treated at 400°C in air for 16 hours. Sustainion X37-50 membrane was used to separate the cathode electrolyte and the anolyte, and the membrane was soaked in 3M NaOH overnight before use. Fluororubber gaskets and PTFE tubes (ColeParmer) were used to construct the battery. Both the cathode electrolyte and the anolyte were circulated by a peristaltic pump at a flow rate of 50mL / min. During the test, O2 was bubbled into the cathode electrolyte and N2 was bubbled into the anolyte continuously at a flow rate of 0.5L / min. The battery performance was tested and recorded by an Arbin battery tester. For 100mA / cm 2 In the tests below, after each discharge process, the cell was rested for self-charging of the catholyte. O2 was bubbled continuously during discharge and self-charging.
[0275] Results and discussion
[0276] When the Zn particles in the anode tank were replaced each time, the voltage first increased rapidly, and then the cell could reach >0.9 V at 10 mA / cm 2 Discharge until all Zn is consumed ( Figure 4 a). The total Zn utilization can reach 90%. In addition, the battery can 2 ( Figure 4 b) and discharge stably at a discharge voltage of up to >0.7V. Figure 4 c, the battery also shows excellent stability for long-term operation. It is worth noting that with multiple zinc additions, the [Zn(OH)4] 2- As the concentration of increases, the self-charging process gradually slows down (voltage recovery becomes slower), limiting the oxidation process of Zn and stabilizing when it reaches saturation. Figure 4 In c, the battery is discharged to a capacity greater than 8 Ah, and [Zn(OH)4] 2- The solubility in 3M NaOH is less than 0.25M, corresponding to ~3Ah in 250mL anolyte. Figure 5 The power performance of the battery is shown. The maximum power density can reach 118 mW / cm 2 .
[0277] Figures 6a-6b show SEM images of Zn particles and Zn powder before and after discharge. After discharge, the shape of the zinc particles changes from a round shape to a needle shape. As shown in Figures 6e-6f, the XRD pattern of the Zn particles changes from Zn (PDF#04-0831) to ZnO (PDF#36-1451). We also compared the XRD patterns and SEM images of the carbon felt electrode used in the anode chamber before and after discharge (Figures 6c-6f). There is almost no ZnO deposited on the carbon felt after discharge, which indicates that the discharge product ZnO is only formed on the surface of the Zn particles. In this way, it solves the electrode passivation problem faced by traditional alkaline Zn-based batteries and enables the Zn metal in the tank to be easily "refueled".
[0278] Example 5.4 Battery ZAFC stack
[0279] Another advantage of RM-ZAFC is its good scalability. We assembled a 4-cell ZAFC stack using 0.2 M Co(III)TiPA / 3 M NaOH (with continuous O2 bubbling) as the catholyte and 0.4 M DHPS / 3 M NaOH (with Zn particles loaded in the anode tank) as the anolyte ( Figure 7 a-b). Figure 7 As shown in FIG. 7a , there is a configuration depicting an exploded view of a 4-cell RM-ZAFC stack. Configuration 700 includes graphite end plates 701 , carbon paper 702 , membrane 703 , gasket 704 , and graphite bipolar plates 705 .
[0280] Assembly and testing of 4-cell ZAFC stack
[0281] for Figure 7 In the 4-cell ZAFC stack, four 1cm 2 Toray carbon paper was used as the electrodes on both sides of each cell. The carbon paper was heat treated at 400 °C for 16 h in air. Sustainion X37-50 membrane was used to separate the catholyte and anolyte, and the membrane was soaked in 3M NaOH overnight before use. The cell performance was tested and recorded by Arbin battery tester.
[0282] Theoretical volume capacity
[0283] Calculate the volume capacity of the anode side of the RM-ZAFB:
[0284] C=C Zn ·U·a·p+C DHPS (1-p)
[0285] Among them C Zn(5,854 Ah / L) is the volume capacity of Zn metal, U(90%) is the utilization of Zn, and a(69 vol.%) is the volume content of Zn in the particles (based on Zn (7.14 g / cm 3 )、Carbon black (1.7 g / cm 3 ) and PVDF (1.78 g / cm 3 ), p(50%) is the volume ratio of solid particles, C DHPS (96Ah / L) is the volume capacity of 1.8M DHPS. C is calculated to be 1,866Ah / L.
[0286] Results and discussion
[0287] The stack can be operated at 10 mA / cm 2 Discharge at a voltage >3.8V ( Figure 7 c). After that, we increased the current density to 100 mA / cm 2 , the battery can still operate at a voltage of about 3V ( Figure 8 ).like Figure 7 As summarized in d, RM-ZAFC has the advantages of working flexibility and scalability as a fuel cell and a flow battery, which makes it suitable for various applications compared with conventional ZAB. In addition, neither expensive electrocatalysts for oxygen reduction reaction (ORR) and hydrogen oxidation reaction nor gas diffusion layers on the air electrode are required, which can greatly reduce costs. The theoretical volume capacity of the system can reach 1,866Ah / L, which is much higher than commercial high-pressure H2 tanks (35MPa: 639Ah / L; 70MPa: 1,278Ah / L). Therefore, the theoretical energy density of the system (~1,900Wh / L) is better than that of alkaline fuel cells. In addition, Zn is much safer than H2 in operation, storage, and transportation. Although alkaline fuel cells can achieve high power density at 80°C, their power density is considerably suppressed at room temperature, even much lower than that of RM-ZAFC.
[0288] Example 6. RM-ZAFC with gas diffusion air electrode as cathode
[0289] The gas diffusion air electrode can also be used as the cathode in the RM-ZAFC. We assembled the ZAFC using Pt / C coated carbon paper as the cathode and supplying dry and 0.5 M DHPS and 6 M KOH as the anolyte loaded with Zn particles in the anode tank ( Fig. 9 ).
[0290] Assembly and testing of a ZAFC with a gas-diffusion air electrode as cathode
[0291] FAAM-15 membrane was used to assemble a flow battery (Scribner, active area 6.7 cm 2 ) to measure the power density under different conditions. Unless otherwise stated, the anolyte used was 0.5 M DHPS and 6 M KOH, the anode flow rate was 20 mL / min, the cathode pressure was 1.5 bar, and the operating temperature was 40°C. Two thermoelectric Peltier cooler modules (Multicomp Pro MPADV-127-140160-S) were used to heat the cell, and a K-type thermocouple probe temperature sensor was sandwiched between the cathode electrode and the membrane to track the cell temperature in real time. The anode electrode consisted of three layers of SGL 29AA carbon paper that had been pretreated at 400°C for 16 hours to enhance its hydrophilicity. The cathode electrode was a Pt loaded with 0.4 mg / cm2 coated with a catalyst. 2 SGL 38BB carbon paper. To prepare the cathode electrode, poly(fluorenyl-co-biphenyl N,N-dimethylpiperidinium) (PFBP14, fluorine ratio of 14%) copolymer was first dissolved in dimethyl sulfoxide (DMSO) and filtered with a 0.45 μm PTFE filter to form a 5% ionomer solution. Subsequently, Pt / C (38.7 wt% Pt, Tanaka, Japan) was added to the ionomer solution and 0.4 mg / cm 2 The prepared slurry was then dispersed in an isopropyl alcohol (IPA) / deionized (DI) water (10:1) solution with a solid-liquid ratio of 5 wt %. After ultrasonic treatment for 1 hour, the prepared ink was sprayed onto the hydrophobic surface of SGL 36BB carbon paper, and then heat-treated at 140 ° C for 12 hours to evaporate DMSO and used as a cathode electrode.
[0292] The ZAFC was operated at 50°C. The cathode was supplied with dry oxygen at a pressure of 1.5 bar and was purged periodically every 10 seconds to prevent water overflow. To avoid clogging of the electrodes by Zn particles or generated ZnO, 2 sheets of carbon felt were set at the outlet of the tank and replaced whenever new particles were added.
[0293] Results and discussion
[0294] Fig. 9 It shows that RM-ZAFC at 50 mA / cm 2 The discharge curve under . After the voltage dropped to the cut-off level of 0V, new Zn particles were added to the tank. It can be observed that the RM-ZAFC can work stably. It provides a high capacity of 14.31Ah with a total Zn utilization of 78.2%. The capacity loss can be attributed to three factors: IR drop, crossover problem caused by high-pressure oxygen, and oxidation of Zn under air conditions.
Claims
1. A redox-mediated metal-air fuel cell system comprising: A redox flow battery comprising: A cathode chamber comprising one of the following: a cathode electrode, and an inlet and an outlet adapted to bubble a gas through said cathode chamber; or a gas diffusion air electrode for oxygen reduction reaction (ORR) that passes supply air through the cathode chamber; an anode chamber comprising an anode electrode and an inlet adapted to receive anolyte from a first tank and an outlet adapted to provide said anolyte to said first tank; an ion selective membrane between the cathode chamber and the anode chamber; and a first tank adapted to contain an anolyte and a redox mediated metal-air fuel cell cartridge and an inlet adapted to receive the anolyte from the anode chamber and an outlet adapted to provide the anolyte to the anode chamber, wherein: The redox mediated metal-air fuel cell cartridge comprises: Box housing; and A composite material comprising A metal selected from alkali metals, alkaline earth metals, aluminum, zinc or iron; Conductive carbon material; and Binder.
2. The system according to claim 1, wherein the metal is selected from one or more selected from the group consisting of Zn, Li, Na, K, Mg, Ca, Al and Fe. The system of claim 2 , wherein the metal is Zn.
4. The system according to any of the preceding claims, wherein the binder is selected from one or more of ethylene cellulose, polyolefins and fluorothermoplastics, optionally wherein the fluorothermoplastics are selected from one or more of the group selected from PTFE and PVDF.
5. The system of claim 4, wherein the binder is PVDF.
6. A system according to any one of the preceding claims, wherein: The metal is present in an amount of 50 to 95 wt %; The conductive carbon material is present in an amount of 2.5 to 30 wt %; The binder is present in an amount of 2.5 to 20 wt%.
7. The system of claim 6, wherein: The metal is present in an amount of 80 to 92 wt %, such as about 90 wt %; The conductive carbon material is present in an amount of 3 to 10 wt %, such as about 5 wt %; The binder is present in an amount of about 3 to 10 wt %, such as about 5 wt %.
8. A system according to any one of the preceding claims, wherein the metal source material is provided in particulate form.
9. The system of any one of the preceding claims, wherein the conductive carbon material is carbon black.
10. The system of any one of the preceding claims, wherein the anode chamber and the first tank further comprise an anolyte comprising an anodic redox mediator and an electrolyte.
11. The system of claim 10, wherein: (a) the anodic redox mediator is selected from one or more of the group consisting of phenazine derivatives, anthraquinone derivatives and alloxazine derivatives, and optionally, the anodic redox mediator is 7,8-dihydroxy-2-phenazine sulfonic acid; and / or (b) the concentration of the anodic redox mediator is 0.01 to 2 M, such as about 0.4 M; and / or (c) The electrolyte is selected from one or more of a NaOH aqueous solution, a KOH aqueous solution (e.g., a concentration of KOH in water is 3 M) and a LiOH aqueous solution (e.g., a concentration of LiOH in water is 3 M), optionally wherein the concentration of NaOH in water is 3 M.
12. The system of claim 10 or claim 11, wherein when the cathode chamber comprises a cathode electrode and an inlet and an outlet adapted for bubbling a gas through the cathode chamber, it further comprises a catholyte comprising a cathode redox mediator and an electrolyte.
13. The system of claim 12, wherein: (a) the cathode redox mediator is selected from one or more of the group consisting of Co(III)TiPA, cobalt triethanolamine complex [Co(TEA)] and anthraquinone-2,6-disulfonate (AQDS); and / or (b) the concentration of the cathode redox mediator is 0.01 to 1 M, such as about 0.2 M; and / or (c) The electrolyte is selected from one or more of a NaOH aqueous solution, a KOH aqueous solution (e.g., a concentration of KOH in water is 3 M) and a LiOH aqueous solution (e.g., a concentration of LiOH in water is 3 M), optionally wherein the concentration of NaOH in water is 3 M.
14. The system of any one of the preceding claims, wherein when the cathode chamber comprises a cathode electrode and an inlet and an outlet adapted to bubble a gas through the cathode chamber, the cathode chamber comprises: cathode casing portion; a cathode housed within said cathode casing portion; and A second tank is adapted to contain a catholyte, an inlet adapted to receive the catholyte from the cathode casing portion and an outlet adapted to provide the catholyte to the cathode casing portion, and an inlet and an outlet adapted to bubble a gas through the second tank.
15. The system according to any one of claims 1 to 10, wherein when the cathode chamber comprises a gas diffusion electrode, the air electrode of the cathode is selected from a porous carbon material coated with an oxygen reduction reaction catalyst, optionally wherein the oxygen reduction catalyst is selected from a platinum group metal (platinum or palladium), a non-platinum group noble metal (such as gold, silver), a carbon-based catalyst (such as a NiCo catalyst with N-doped carbon nanotubes as a carrier, a catalyst modified with dispersed Fe-N x One or more of the group consisting of substances and B-centered porous carbon).
16. A redox-mediated metal-air fuel cell cartridge comprising: Box housing; and A composite material comprising: A metal selected from alkali metals, alkaline earth metals, aluminum, zinc or iron; Conductive carbon materials; and Binder. 17 . The cartridge according to claim 16 , wherein the metal is one or more selected from the group consisting of Zn, Li, Na, K, Mg, Ca, Al, and Fe.
18. The cartridge of claim 17, wherein the metal is Zn.
19. The box according to any one of claims 16 to 18, wherein the binder is selected from one or more of ethylene cellulose, polyolefins and fluorothermoplastics, optionally, wherein the fluorothermoplastics are selected from one or more of the group selected from PTFE and PVDF.
20. The cartridge of claim 19, wherein the binder is PVDF.
21. A cartridge according to any one of claims 16 to 20, wherein: The metal is present in an amount of 50 to 95 wt %; The conductive carbon material is present in an amount of 2.5 to 30 wt %; The binder is present in an amount of 2.5 to 20 wt%.
22. The cartridge of claim 21, wherein: The metal is present in an amount of 80 to 92 wt %, such as about 90 wt %; The conductive carbon material is present in an amount of 3 to 10 wt %, such as about 5 wt %; The binder is present in an amount of about 3 to 10 wt %, such as about 5 wt %.
23. A cartridge according to any one of claims 16 to 22, wherein the metal source material is provided in particulate form.
24. A cartridge according to any one of claims 16 to 23, wherein the conductive carbon material is carbon black.
25. A method for supplying metal in a redox mediated metal-air fuel cell system, comprising: A redox flow battery comprising: A cathode chamber comprising one of the following: a cathode electrode, and an inlet and an outlet adapted to bubble a gas through said cathode chamber; an anode chamber comprising an anode electrode, an anolyte comprising an anodic redox mediator and an electrolyte, and an inlet adapted to receive the anolyte from a first tank and an outlet adapted to provide the anolyte to the first tank; an ion selective membrane between the cathode chamber and the anode chamber; and a first tank comprising the anolyte, a redox mediated metal-air fuel cell cartridge as claimed in any one of claims 16 to 24 and an inlet adapted to receive the anolyte from the anode chamber and an outlet adapted to provide the anolyte to the anode chamber, wherein the method involves: (a) circulating the anolyte from the first tank to the anode chamber and back again, and supplying gas to the catholyte; and (b) When the redox mediated metal-air fuel cell cartridge is depleted, replacing the redox mediated metal-air fuel cell cartridge.
26. The method of claim 25, wherein: (a) when the cathode chamber comprises a cathode electrode and an inlet and an outlet adapted to bubble a gas through the cathode chamber, the cathode redox mediator is selected from one or more of the group consisting of Co(III)TiPA, cobalt triethanolamine complex [Co(TEA)] and anthraquinone-2,6-disulfonate (AQDS), or; (b) when the cathode chamber comprises a cathode electrode and an inlet and an outlet adapted to bubble a gas through the cathode chamber, the concentration of the cathode redox mediator is 0.01 to 1 M, such as about 0.2 M; and / or (c) the anodic redox mediator is selected from one or more of the group consisting of phenazine derivatives, anthraquinone derivatives and alloxazine derivatives, optionally wherein the anodic redox mediator is 7,8-dihydroxy-2-phenazine sulfonic acid; and / or (d) the concentration of the anodic redox mediator is 0.01 to 2 M, such as about 0.4 M; and / or (e) The electrolyte is selected from one or more of a NaOH aqueous solution, a KOH aqueous solution (e.g., a concentration of KOH in water is 3 M) and a LiOH aqueous solution (e.g., a concentration of LiOH in water is 3 M), optionally wherein the concentration of NaOH in water is 3 M.
27. A method according to claim 25 or claim 26, wherein when the cathode chamber comprises a cathode electrode and an inlet and an outlet adapted to bubble a gas through the cathode chamber, the cathode chamber comprises: cathode casing portion; a cathode housed within said cathode casing portion; and A second tank is adapted to contain a catholyte, an inlet adapted to receive the catholyte from the cathode casing portion and an outlet adapted to provide the catholyte to the cathode casing portion, and an inlet and an outlet adapted to bubble a gas through the second tank.
28. The method of claim 25, wherein: (a) When the cathode chamber comprises a gas diffusion electrode for oxygen reduction reaction that allows air or oxygen to be supplied directly through the cathode chamber, the air electrode of the cathode is selected from a porous carbon material coated with an oxygen reduction reaction catalyst, optionally, wherein the oxygen reduction catalyst is selected from a platinum group metal (platinum or palladium), a non-platinum group noble metal (such as gold, silver), a carbon-based catalyst (such as a NiCo catalyst with N-doped carbon nanotubes as a carrier, a catalyst modified with dispersed Fe-N x One or more of the group consisting of: (b) the anodic redox mediator is selected from one or more of the group consisting of phenazine derivatives, anthraquinone derivatives and alloxazine derivatives, optionally wherein the anodic redox mediator is 7,8-dihydroxy-2-phenazine sulfonic acid; and / or (c) the concentration of the anodic redox mediator is 0.01 to 2 M, such as about 0.4 M; and / or (d) The electrolyte is selected from one or more of a NaOH aqueous solution, a KOH aqueous solution (e.g., a concentration of KOH in water is 3 M) and a LiOH aqueous solution (e.g., a concentration of LiOH in water is 3 M), optionally wherein the concentration of NaOH in water is 3 M.
29. A metal-air fuel cell metal source material, wherein the source material comprises: A metal selected from alkali metals, alkaline earth metals, aluminum, zinc or iron; Conductive carbon material; and Binder.
30. A composite material comprising: A metal selected from alkali metals, alkaline earth metals, aluminum, zinc or iron; Conductive carbon material; and Binder.
31. The metal source material according to claim 29 or the composite material according to claim 28, wherein the metal is one or more selected from the group consisting of Zn, Li, Na, K, Mg, Ca, Al and Fe.
32. The metal source material or the composite material of claim 31 , wherein the metal is Zn.
33. The metal source material according to any one of claims 29, 31 and 32 or the composite material according to any one of claims 30 to 32, wherein the binder is selected from one or more of ethylene cellulose, polyolefins and fluorinated thermoplastics, optionally, wherein the fluorinated thermoplastics are selected from one or more of the group selected from polytetrafluoroethylene (PTFE) and polyvinylidene fluoride (PVDF).
34. The metal source material or the composite material according to claim 33, wherein the binder is PVDF.
35. The metal source material according to any one of claims 29 and 31 to 34 or the composite material according to any one of claims 30 to 34, wherein: The metal is present in an amount of 50 to 95 wt %; The carbon black is present in an amount of 2.5 to 30 wt %; and The binder is present in an amount of 2.5 to 20 wt%.
36. The metal source material or the composite material according to claim 35, wherein: The metal is present in an amount of 80 to 92 wt %, such as about 90 wt %; The conductive carbon material is present in an amount of 3 to 10 wt%, such as about 5 wt%; and The binder is present in an amount of about 3 to 10 wt %, such as about 5 wt %.
37. The metal source material according to any one of claims 29 and 31 to 36 or the composite material according to any one of claims 30 to 36, wherein the metal source material is provided in particulate form.
38. The metal source material of any one of claims 29 and 31 to 37 or the composite material of any one of claims 30 to 37, wherein the conductive carbon material is carbon black.